Obstacles Facing Teachers Of Physical And Sports Education And Their Implications For Achieving The Curriculum Goals From The Viewpoint Of Teachers Of Intermediate And Secondary Education - Benguesmi , Yakoub; Benguesmi , Tarek (sports creativity, 2025)
This study aimed to detect various obstacles that may face teachers and prevent them from effectively achieving the goals of the physical and sport education program in the middle and secondary education stage. It also aims to identify the differences between the members of the sample based on the different variables of: years of professional experience, scientific qualification, and the workplace. To achieve this, the two researchers used the analytical descriptive method to find out the point of views of physical education teachers regarding these obstacles by designing a survey for collecting the data, which was divided into Four axis. The two researchers relied on the random sample, where 100 surveys were distributed to the teachers of the middle and secondary stages, from which 86 of the data was retrieved, with a response rate of about 86%. To achieve the study's objective, the two researchers used several statistical methods, including Alpha Cronbach, to ensure consistency, repetition and percentages for describing study variables, and the arithmetic mean for determining the level of study variables answers. After the data for the study had been emptied, disaggregated and analyzed, the study's results has found that the most severe constraints were the lack of available means and capabilities, the least severe of which was administrative and organizational constraints. The study also found that there were no differences due to years of professional experience, scientific qualification and the workplace.